STRUCTURAL STRUCTURE OF PHARMACEUTICAL TERMS (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the structural structure of pharmaceutical terms based on an in-depth linguistic analysis. The morphological elements (prefix, suffix, root) of terms, their semantic connotations, morphosyntactic and pragmatic properties are considered. The relationship with the international system of terms is also studied separately.